Direct, indirect and pleiotropic effects of candidate genes on internalizing disorder psychopathology. Issue 10 (July 2015) - Hettema, J. M.; Chen, X.; Sun, C.; Brown, T. A.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Twin studies of internalizing disorders suggest that their high co-morbidity is partially explained by shared genetic risk. Few studies have investigated pleiotropic effects of well-validated candidate genes across phenotypes. Method Subjects were 928 Caucasian patients who presented to an out-patient clinic specializing in the assessment and treatment of anxiety and mood disorders. We constructed latent dimensional phenotypes across the internalizing spectrum (neuroticism, extraversion, depression, generalized anxiety, panic/agoraphobia, social phobia, post-traumatic stress, and obsessions–compulsions) by combining diagnostic criteria with other clinical indicators. We selected multiple variants in four evidence-based candidate genes (SLC6A4, COMT, GAD1, RGS2) with previously reported effects on several of these phenotypes. We conducted genetic association testing of their direct and indirect effects as well as gene × stress interactions (G × E). Results We detected 19 nominally significant main effect associations for the 10 polymorphisms tested among the eight phenotypes (24%). These were generally phenotype non-specific, showing pleiotropic effects across multiple domains. The majority of observed sharing was between depression, panic disorder, and post-traumatic stress disorder. Some of these were best explained by mediational models in which genes increase liability for disorders indirectly via their effects on temperament. Limited G × E effects were detected between variants in SLC6A4 and both panic/agoraphobia and post-traumatic stress. Conclusions Examining just a few candidate genes for their potential roles in internalizing phenotypes, we found moderate support for the shared effects of several polymorphisms. These findings highlight the richness and complexity by which genes potentially contribute to psychopathology via pleiotropy, moderation by stress, and mediation by temperament.